2020
DOI: 10.2478/subboec-2020-0014
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Financial Inclusion in Southern Africa

Abstract: The study sought to establish the drivers of financial inclusion in Southern Africa with a specific focus on South Africa. Financial inclusion has been a topic of global interest due to the negative impact of financial exclusion in addressing socio-economic issues like poverty. Using the logit model, the study discovered that financial inclusion is driven by age, education level, the total salary proxy of income, race, gender, and marital status. The variable gender was the only factor with a negative influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Mhlanga and Denhere (2020) examined the drivers of financial inclusion in South Africa. Considering bank account ownership as the proxy variable of financial inclusion, they used data from the South Africa 2018 General Household Survey (GHS) dataset to perform logit estimations.…”
mentioning
confidence: 99%
“…Mhlanga and Denhere (2020) examined the drivers of financial inclusion in South Africa. Considering bank account ownership as the proxy variable of financial inclusion, they used data from the South Africa 2018 General Household Survey (GHS) dataset to perform logit estimations.…”
mentioning
confidence: 99%
“…Various studies have been conducted in this area (Amaeshi et al, 2007;Adewale et al, 2012;Mhlanga & Denhere, 2020), below presents the chronology of major studies related to this research in order to assess and identify the research gap. In South Africa, Wentzel et al (2016) investigated the factors impacting FE and found that the most significant factors associated with being financially excluded in South Africa were educational level, the primary source of income, age, home language, and the number of dependents.…”
Section: Review Of Empirical Studiesmentioning
confidence: 99%
“…Hence Zimbabwe, being one of the African countries, is not an exception when it comes to corruption, which has been identified as one of the causes of liquidity crisis in the country. The bond notes referred to as the "surrogate currency" faced resistance when they were introduced because both the business community and the public conceived this scenario as the reintroduction of the Zimbabwean dollar (Southall, 2017;Mhlanga, 2021). As indicated earlier, the Zimbabwean dollar had a history of failure, and depositors began to withdraw their US dollar cash balances from banks in fear of being prejudiced.…”
Section: The Liquidity Crisis In Zimbabwementioning
confidence: 99%